Analysis of Chemical Contaminants in Food (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
How many times have we thought with concern about the possible contamination of food? Pollution, agricultural treatments, technological treatments, and packaging are the best-known human sources of toxic substances as food contaminants. The present book contains 11 original research papers representing various approaches of identifying and measuring toxic residues in food materials. The analytical determination of food contaminants is an indispensable tool in characterizing the adverse effects and unexpected toxicity related to food intake. No risk assessment would be possible without data from the analysis of food contaminants. This Special Issue is an interesting overview of recent methods and is highly representative of a broad worldwide outline, collecting authors from ten different countries and four continents. Very different toxics are described, from volatile organic compounds to heavy metals and from highly polar chemicals to classical organic contaminants. A wide range of analytical techniques are portrayed, including sample preparation and clean-up methodologies, classical chromatographic and hyphenated spectroscopies, and the latest high-resolution mass spectrometry applications. The presented works consider a varied selection of foods: the studied matrices are meat, fishery products, fruits, and miscellaneous beverages.